Almost statistical convergence of order ? - Et, Mikail; Altin, Yavuz; Colak, Rifat (Univ Estadual Maringa, Pro-Reitoria Pesquisa Pos-Graduacao, 2015)
In this paper, we introduce the concept (S) over cap (alpha)(lambda) - statistical convergence of order alpha. Also some relations between (S) over cap (alpha)(lambda) - statistical convergence of order alpha and strong (w) over cap (alpha)(p)(lambda) - summability of order alpha are given. Furthermore some relations between the spaces (w) over cap (alpha)(p)[lambda,M] and (S) over cap (alpha)(lambda) are examined.
Quase convergência estatística da order ?
Keywords: statistical convergence; almost convergence; Cesaro summability